Dependence of milk productivity and reproductive capacity of cows on their growth intensity under different conditions of maintenance - O. Y. Admin; N. G. Admina; А. P. Paliy; O. V. Pavlichenko; O. S. Panasenko; H. A. Fotina; L. M. Kovalenko; V. I. Risovaniy (Regulatory Mechanisms in Biosystems, 2025)
The growth rate of replacement heifers significantly impacts their reproductive capacity and subsequent milk production. Therefore, breeding methods should be evidence-based to maximize the productivity of animal s throughout their lives. To study this issue, we analyzed the zootechnical records of dairy cattle breeding enterprises in the Kharkiv and Poltava region s of Ukraine. We found that production technology on a particular farm most influenced heifer growth intensity. The influence of the "farm" factor on heifers' live weight at 3 months of age was 6.4%; at 6 months, 3.8%; at 9 months, 6.1%; at 12 months, 7.0%; and at 15 months, 13.2%. The youngest age at first insemination was observed in heifers from the Kutuzivka and Stepne farms due to their accelerated growth. Heifers from the "Gontarivka" and "Agroprogress" farms were inseminated later (after 3 months). Except for the SE RF "Named after Decabrysty", all farms showed a tendency to reduce the service period duration with an i n crease in lactations. This indicates similar selection methods on these farms. The results of the study showed that animals with the greatest live weight gain were significantly younger at first insemination. The milk yield of first-born heifers positively correlated with live weight at 15 months of age. The early maturity of replacement heifers contributes to the intensive reproduction of the herd and increases the profitability of dairy farming. Further research should determine the effect of growth intensity on cow fertility and calf survival.